Why All Teachers Matter: The Relationship Between Long-Term Teacher and Classroom Quality and Children's Reading Achievement. Issue 2 (3rd April 2017) - Palacios, Natalia
ABSTRACT: This study uses the Early Childhood Longitudinal Study-Kindergarten Cohort to examine the influence that teachers and classrooms have on children's short- and long-term reading achievement trajectories throughout the elementary school years. The analytic sample in the 1st grade is 16, 604 children nested within 5, 029 teachers, the 3rd-grade sample includes 14, 281 children nested within 6, 023 teachers, and the 5th-grade sample includes 11, 233 children nested within 4, 734 teachers. Children's previous teacher and classroom experiences are associated with a small but long-term influence on children's reading achievement, explaining 5% to 10% of variability in student achievement at later time points. In contrast, the measures of concurrent teacher characteristics and qualifications, as well as concurrent instructional practices, used in this study were inconsistently associated with reading achievement in 1st, 3rd, and 5th grades.